HUBUNGAN KECANDUAN GAME ONLINE CLASH OF CLANS TERHADAP PERILAKU SOSIAL (Studi Kasus Game Online Clash Of Clans pada Mahasiswa Sosiologi Fakultas Ilmu Sosial Dan Politik Universitas Riau) - Okto Dinata; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Students are part of the community and academic community needs to be prepared with the advancement of technology era especially new media, so that students are able to use media intelligently and effectively. New media should be a mandatory knowledge that must be mastered by every student, especially students of Riau University. The online game clash of clans is a game that can be accessed by many players, where the machines used by players are connected by a network. However, because this online clash of clans game is an online game game that is played on smartphone, making it easier for players to play this game anywhere and anytime, and require a long duration of playing in completing this clash of clans online game game, then there is It is likely that this clash of clans online game is causing addiction to its players.The concept of theory that researchers use is the theory of addiction. Addiction is an ongoing unhealthy behavior that is difficult to end by the individual concerned (Yee, 2006). Unhealthy behavior can harm the individual and such behavior is seen in online game players. Addictive behavior of online games can be caused by the availability and increasing types of games on the market that increasingly rapidly parallel with the development of technology (Jessica, 1999). Clash of Clans game is a pleasure in playing because it gives a sense of satisfaction, so there is a feeling to repeat again fun activities when playing online games .. This research is descriptive qualitative research.Based on interviews with informants, stating that playing online games makes them feel bound by online games, is a necessity for an ever-increasing amount of time, making efforts to control, reduce, or stop playing online games but to no avail, to feel uneasy, Moody, depressed, or irritable when trying to reduce or stop playing online games. Play online games as a way to escape from problems. From the interview can also be concluded that by playing online games, informants indirectly continuously carried over the game online, so they so rarely hang out with friends or relatives around their neighborhood.